(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
This research was conducted to determine the role of humic acid(HA) and salicylic acid (SA) on growth, flowering and bulb production of Tuberose (Polianthes tuberosa) fertilized with organic manure. The study included five treatments(T1:control,T2:farmer treatment,T3:addition of 1.5 g/l/m2 humic acid to the soil, T4: foliar spray with(0.2) g/l SA, T5 = T3 + T4). The results showed that the application of HA and SA in addition of organic manure(T5) promote vegetative growth, flowering and reduce the time of spike emergence. Flower quality and vase flower life were improved as well in the two flower harvest. The results showed as well that T5 gave higher reproductive index(28.6 bulbs/plant) compared to the control(22 bulbs/plant). هدف هذا البحث إلى دراسة تأثير المعاملة بحمضي الهيوميك والصفصاف في النمو الخضري والإزهار ومعامل التكاثر لنبات الزنبق (Polianthes tuberosa) المسمد بالسماد العضوي. شملت الدراسة خمس معاملات (T1: :شاهد، T2: معاملة المزارع (تسميد عضوي + معدني)، T3: الري بحمض الهيوميك تركيز 1.5 غ/ل/م2، T4: الرش بحمض الصفصاف بتركيز 0.2غ/ل، T5= T3+T4). أظهرت النتائج أن استخدام حمضي الهيوميك والصفصاف معاً بوجود السماد العضوي (T5) ساهم بشكل إيجابي في كافة مؤشرات النمو الخضري، إضافة إلى دوره في التبكير بتمايز الشماريخ الزهرية وبدء الازهار، تحسين نوعية الأزهار وإطالة عمر الأزهار في مرحلة ما بعد القطاف وذلك لدفعتي الازهار الأولى والثانية. كما حققت المعاملة (T5) أفضل معامل تكاثر (28.6 درينة\نبات) مقابل (22 درينة\نبات) في معاملة الشاهدT1)).